2011
DOI: 10.2217/fmb.11.23
|View full text |Cite
|
Sign up to set email alerts
|

Global Spread of Drug-Resistant Acinetobacter Baumannii : Molecular Epidemiology And Management Of Antimicrobial Resistance

Abstract: Acinetobacter baumannii is an opportunistic Gram-negative pathogen with increasing relevance in a variety of hospital-acquired infections especially among intensive care unit patients. Resistance to antimicrobial agents is the main reason for A. baumannii spread. A. baumannii outbreaks described worldwide are caused by a limited number of genotypic clusters of multidrug-resistant strains that successfully spread among hospitals of different cities and countries. In this article, we will focus on the mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(104 citation statements)
references
References 163 publications
(327 reference statements)
2
98
0
4
Order By: Relevance
“…In this study, most of the isolates showed carbapenem associated multidrug resistance, which was similar as other areas of the United States and worldwide [9] [11] [30], and more sadly some of them conferred intermediate levels of polymyxin resistance. Outbreaks of polymyxin associated carbapenem resistant A. baumannii should alert in this area.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In this study, most of the isolates showed carbapenem associated multidrug resistance, which was similar as other areas of the United States and worldwide [9] [11] [30], and more sadly some of them conferred intermediate levels of polymyxin resistance. Outbreaks of polymyxin associated carbapenem resistant A. baumannii should alert in this area.…”
Section: Discussionsupporting
confidence: 78%
“…Outbreaks of carbapenem associated multidrug resistant A. baumannii may be the most problematic issue to treat the infected patients since the only viable therapeutic option for this infection is polymyxins [9], but polymyxins cause neuro-and nephro-toxicity [27] and polymyxin selection pressure can readily develop polymyxin resistant A. baumannii [28] [29]. In this study, most of the isolates showed carbapenem associated multidrug resistance, which was similar as other areas of the United States and worldwide [9] [11] [30], and more sadly some of them conferred intermediate levels of polymyxin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…NIHR Journals Library www.journalslibrary.nihr.ac.uk the changing epidemiology of HCAIs, 589,[607][608][609][610] exemplified by the rise of MRSA and extended-spectrum beta-lactamase (ESBL)-producing strains of Escherichia coli and Klebsiella pneumonia. 609,[611][612][613][614][615][616][617][618][619] In the NHS, following major outbreaks of hospital-acquired (nosocomial) infection, 620 national targets for the reduction of MRSA bacteremias (blood infections) and C. difficile (gastrointestinal) infection are supported by enhanced mandatory surveillance.…”
Section: Reducing Health-care-associated Infectionmentioning
confidence: 99%
“…In order to determine the outcome of infections more attention should be paid to the interaction between A. baumannii and the host epithelial cells (4,10). The adherence potential of A. baumannii to human bronchial epithelial cells and its resistance to major antimicrobial agents explain its survival in the medical environment and the human host (11). A few molecular factors are required for A. baumannii virulence in humans.…”
Section: Introductionmentioning
confidence: 99%